Pathogenic variants in the CYP21A2 gene cause isolated autosomal dominant congenital posterior polar cataracts. (4th March 2022) - Berry, Vanita; Pontikos, Nikolas; Ionides, Alex; Kalitzeos, Angelos; Quinlan, Roy A.; Michaelides, Michel
ABSTRACT: Background: Congenital cataracts are the most common cause of visual impairment worldwide. Inherited cataract is a clinically and genetically heterogeneous disease. Here we report disease-causing variants in a novel gene, CYP21A2, causing autosomal dominant posterior polar cataract. Variants in this gene are known to cause autosomal recessive congenital adrenal hyperplasia (CAH). Methods: Using whole-exome sequencing (WES), we have identified disease-causing sequence variants in two families of British and Irish origin, and in two isolated cases of Asian-Indian and British origin. Bioinformatics analysis confirmed these variants as rare with damaging pathogenicity scores. Segregation was tested within the families using direct Sanger sequencing. Results: A nonsense variant NM_000500.9 c.955 C > T; p.Q319* was identified in CYP21A2 in two families with posterior polar cataract and in an isolated case with unspecified congenital cataract phenotype. This is the same variant previously linked to CAH and identified as Q318* in the literature. We have also identified a rare missense variant NM_000500.9 c.770 T > C; p.M257T in an isolated case with unspecified congenital cataract phenotype. Conclusion: This is the first report of separate sequence variants in CYP21A2 associated with congenital cataract. Our findings extend the genetic basis for congenital cataract and add to the phenotypic spectrum of CYP21A2 variants and particularly the CAH associated Q318* variant. CYP21A2 has a significant role in mineralo- and gluco-corticoid biosynthesis. These findings suggest that CYP21A2 may be important for extra-adrenal biosynthesis of aldosterone and cortisol in the eye lens.